The Effect of Motivation and Compensation on The Performance of Honorer Employees in Type a Simbuang Terminal Service Units Ministry of Transportation of The Republic of Indonesia in Mamuju District - Mu’fidatul Nurul Hajjad; Yati Heryati; Andi Nursiskawati Siangka; Muhtar Mudo (PINISI Discretion Review, 2021)
Every agency certainly wants good employee or employee performance. In government agencies such as the Simbuang Type A Terminal of the Ministry of Transportation of the Republic of Indonesia in Mamuju Regency, there are temporary employees who are employed as terminal managers. Due to his status as an honorary employee, his salary scheme is certainly different from that of his colleague who is a civil servant. This study seeks to examine the effect of motivation and compensation obtained by honorary employees at the bus terminal on their performance. This study is a quantitative study that tested two variables and analyzed using multiple linear regression. Sources of data are respondents who are temporary employees at Terminal Type A Simbuang the Ministry of Transportation of the Republic of Indonesia in Mamuju Regency. Data collection techniques used are questionnaires, observation, and documentation studies. The results showed that the motivation variable and the compensation variable had a significant effect either partially or simultaneously on the performance given by the honorary employees.